MODERN APPROACHES IN COMPLEX LABORATORY TESTING FOR DIPHTHERIA - L. A. Kraeva; E. A. Alekseeva; G. Y. Tseneva; L. A. Lipatova; G. I. Bespalova (Инфекция и иммунитет, 2014)
Abstract. The criteria of reliable validation of population protection against diphtheria on the base of two indices including quantity of antitoxic antibodies to diphtheria and avidity index have been established. For this purposes it was proposed to use the modified variant of ELISA allowed to detect both indices simultaneously. The formula of probable development of diphtheria in case of the close contact with patients or Corynebacterium diphtheriae bacteria carriers as well as determination of revaccination time have been proposed. The authors developed “The algorithm of population immunity control and assessment of non-susceptibility to diphtheria” and “The algorithm of micro biological testing of clinical samples for C. diphtheriae”.